Conceptual dimensions in technology use and acceptance models - Pinheiro, A.; Oliveira, A.; Alturas, B. (EDULEARN22 Proceedings, 2022)
Advances in information and communication technologies, especially online digital applications, provide new experiences at a personal, community and even social level. To understand how digital technologies influence users' perceptions, what they value most and why they adopt them, conceptual models are developed – and tested – based on predicted causal relationships between latent dimensions, in each context. Digital games are used in the most diverse contexts and by all age groups. Given their relevance in terms of play, fun, or, eventually, in terms of learning or socialization, they have conquered a legion of fans. At the same time, and consequently, the characteristics of games, the role they play for users, and the influence they have on human behavior, are investigated by a growing number of authors, namely in topics, such as, cognition and learning, health and well-being, socialization, advantages, and disadvantages of its use. Digital games derive from the evolution of electronic games, incorporate new technologies and run-on game consoles, computers, cell phones, tablets, and other mobile devices. In this context, we emphasize the use of digital games in teaching and learning among adults. The main objective of this work was to find out what are the more important dimensions in previous studies that analyzed the use of digital games by adults, in the context of teaching and learning. To achieve this goal, we analyzed the most relevant articles that propose and evaluate technology acceptance models in this research topic and were published in the last fifteen years - according to pre-defined inclusion criteria. In this systematic review, we had selected forty-eight scientific papers (indexed), from which the abstracts and keywords were analyzed with textual content analysis techniques, using the Iramuteq 0.7 alpha 2 software - through Descending Hierarchical Classification (DHC), Similitude Analysis and Correspondence Factor Analysis. We considered the following inclusion criteria: articles published in journals or proceedings of international conferences (indexed by Scopus or WoS), between 2006 and 2021, that have at least one significant keyword (serious games, social games, mobile games, or computer games), and are focused on the use and acceptance of digital games among adults – so, only studies that explore technology acceptance models in adults’ samples were considered. The results highlighted the dimensions that have been considered as most relevant in the use of digital games among adults, particularly in terms of teaching and learning. This is also an important contribution at an academic-scientific level, to propose a new conceptual model to explain the adoption of digital games among adults in a broader context – giving us suggestions for future work, such as the possibility of learning through socialization while using online digital games.